Development of Sepak Takraw Model Through TGFU to Improve Basic Athlete Junior in Playing Sepak Takraw - Arizky Ramadhan; Iyakrus Iyakrus; Yahya Eko Nopiyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The objective of this study is to provide an overview and assess the viability of developing the Sepak takraw model. The research employs the ADDIE R&D research method. The design for developing the Sepak takraw model through TGfU comprises several activity components, namely game, net, wall, and target invasion. The sample for this study consisted of 34 university students, who were subjected to an effectiveness test. The pre-test average score was 22.06 and the post-test average score after being given Sepak takraw model through TGfU was  34.24,  which  means  that  there  was  an increase in the results from the pretest to the post-test. The results of the correlation test show a p-value of  0.000 (< 0.005), which means there is a correlation between the increase in technical skills in the given model. So it can be concluded that the development of the sepak takraw model through tgfu is effective for use in sepak takraw learning to improve basic skills.